Investigación aplicada en Ingeniería - Suárez López, Diana (Corporación Universitaria Americana, 2018)
This book is a compendium of chapters resulting from research covering various areas of systems engineering, including topics such as: Information and Communication Technologies (ICT), Capability and Maturity Model Integrated (CMMI), Enterprise Architecture, Geo-referencing services, Geographic Information Systems (GIS), technologies applied to the health sector, box culverts, among others.